Lakhminandan Bora‟sKayakalpaas a Science Fiction: An Analysis - Neog, Pronita (International Journal of Psychosocial Rehabilitation, 2020)
Literature is the artful combination of imagination and realism. Apart from other sources of literature, there are plenty of works written on science. Now-a-days, science based literature is regarded as an established branch of literature. This form of literature has developed from the early twentieth century. In the background of the society, science fiction is written on the incident which is not occurred at present but might befall in future or happened in the past and if these incidents arise out of social changes borne out of the growth of science and technology, then these stories can be termed as science fiction. That means this type of fiction can not be written without any scientific base. Lakhminandan Bora’s book Kayakalpa(awarded with one of the most elevated recompense in Indian literature ‘Saraswati Award’) is undoubtedly a popular science based novel.